The Moderation Effect of Risk Governance Structure on Risk Management and Its Impact on Financial and Social Performance of Islamic Banks in Indonesia - Kurniawan, Ferdian Ari; Hanggraeni, Dewi (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2024)
Introduction to The Problem: Risk management is critical for Islamic banks, which must navigate financial and operational risks while adhering to Sharia principles. Understanding how risk governance structures influence the effectiveness of risk management in enhancing both financial and social performance is essential. Purpose/Objective Study: This study aims to explore the moderation effect of risk governance structures on the relationship between risk management—specifically insolvency risk, financing risk, and operational risk—and the financial and social performance of Islamic banks in Indonesia. Design/Methodology/Approach: The research utilized a dynamic panel data regression method to analyze data extracted from the annual reports of 11 Islamic commercial banks spanning from 2012 to 2021. Findings: The study finds that certain risk governance structures, including the size of the audit committee, its independence, the expertise of its members, and the frequency of its meetings, as well as the quality of external audits, significantly enhance the impact of risk management on both the financial and social performance of Islamic banks. Additionally, specific structures unique to Islamic banks, such as the Sharia Supervisory Board size and the frequency of their meetings, also strengthen this effect.